Programação das operações de transporte de derivados de petróleo em redes de dutos - Felizari, Luiz Carlos (2009)
This work addresses an optimisation structure to support the operational decision-making of scheduling activities in a real world pipeline network. The used scenario to transport petroleum derivaties involves 9 areas (3 refineries, 1 harbour, and 5 distribution centres). Thus, the computational burden for determining a short-term scheduling within the considered scenario is a relevant issue. A decomposition approach is proposed to address such real-world problem. A continuous-time mixed integer linear programming model (MILP) is studied and used to determine the operational short-term scheduling. In this context of multilevel hierarchical structure, sequencing of activities are carried out by a heuristic algorithm which can fail for some particular cases. Thus, we propose to reformulate the sequencing problem by using high-level constructs of Constraint Logic Programming (CLP). The optimisation structure has been extensively tested in typical operational scenarios which, involve in general more than 100 batches. The scheduling horizon is considered to be about 1 month. Many insights have been derived from the obtained solutions, and the proposed approach can support the decision-making process.